Navigating Digital Disruptions: Internalizing Pancasila Values in Islamic Primary School Character Education - Yualita, Putri Nur Wahidah; Rahmawati Tri Utami; Icha Dwi Febriana; Isna Fatimatuz Zahroh (Yayasan Cerdas Pedia Indonesia, 2025)
The rapid digitalization of education creates a